1D and 2D Nuclear magnetic resonance (NMR) relaxation behaviors of protons in clay, kerogen and oil-bearing shale rocks. (April 2020) - Zhang, Pengfei; Lu, Shuangfang; Li, Junqian; Chang, Xiangchun
Abstract: Few 1D T 2 and 2D T 1 - T 2 Nuclear magnetic resonance (NMR) studies have focused on oil-bearing shales with complex constituents and a deeper understanding of the NMR relaxation behaviors of oil confined in shale is needed. In this paper, a series of T 2 and T 1 - T 2 NMR experiments were performed on oil-bearing shale and its components (clay minerals and kerogen) to obtain the T 1 - T 2 fluid typing chart and analyze the adsorbed and free oil in shale. The results were as follows: five types of water (bound, adsorbed, free, crystal and structural water) in clay minerals were qualitatively identified and described by the specific T 2 to T 1 / T 2 ratio values, and T 1 - T 2 maps were used to qualitatively indicate the clay type. The T 1 - T 2 fluid typing chart containing the signatures of 8 proton populations in oil-bearing shale was defined and included bulk liquid, macropore (>1000 nm) oil, nanopore (<1000 nm) oil, and free water in clay minerals or kerogen, shale pore water, bound water in clay minerals, kerogen and crystal water. Adsorbed oil was mainly confined in nanopores, especially micropores smaller than 100 nm, while free oil composed of movable and irreducible oil was predominant in mesopores (100–1000 nm) and macropores. Furthermore, the proportion of irreducible oil gradually decreased and that of movable oil gradually increased from mesopores to macropores. The results demonstrate that the T 1 - T 2 NMR technique may be an effective method for the assessment of fluid distributions and proton mobility and has potential applications for the characterization of shale oil occurrence states. Highlights: Five types of water in clay minerals were qualitatively identified by the specific T2 to T1/T2 ratio values. The T1-T2 fluid typing chart containing the signatures of 8 proton populations in oil-bearing shale was defined. Shale oil occurrence states in different size pores were qualitatively revealed.